Importance of Market Orientation and Product Innovation in Competitive Advantage for Improving Marketing Performance - Afifah Fadila (FEBI UIN Sunan Kalijaga, 2021)
This study aims to see how the role of product innovation and market orientation by Apple and Samsung companies in achieving competitive advantage to improve marketing performance. The method used in this study is a qualitative method with data sources derived from the opinions of relevant experts or researchers and then reviewed by researchers with a literature review to then draw a conclusion. The results show that Samsung is superior to Apple because Apple only emphasizes iPhone products with a focus on market orientation, while Samsung always innovates and is market-oriented with a variety of products. But both still excel in the world market. So that innovation and market orientation greatly affect the success of their marketing performance.